2018
DOI: 10.26434/chemrxiv.7234721.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cavity Catalysis ‒Accelerating Reactions under Vibrational Strong Coupling‒

Abstract: <p>In conventional catalysis the reactants interact with specific sites of the catalyst in such a way that the reaction barrier is lowered and the reaction rate is accelerated. Here we take a radically different approach to catalysis by strongly coupling the vibrations of the reactants to the vacuum electromagnetic field of a cavity. To demonstrate the possibility of such cavity catalysis, we have studied hydrolysis reactions under strong coupling of the OH stretching mode of water to a Fabry-Pérot (FP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…9a. This occurs because states |Ψ 22 and |Ψ 23 do have uncoupled components that interact via the photonic selection rule ∆n ± 1, but their weight in the eigenfunction is comparatively small.…”
Section: Energy Crossings In the Excited Polariton Manifoldmentioning
confidence: 99%
See 3 more Smart Citations
“…9a. This occurs because states |Ψ 22 and |Ψ 23 do have uncoupled components that interact via the photonic selection rule ∆n ± 1, but their weight in the eigenfunction is comparatively small.…”
Section: Energy Crossings In the Excited Polariton Manifoldmentioning
confidence: 99%
“…Several recent studies on vibrational strong coupling (VSC) within the ground electronic state have shown that chemical reactions can proceed through novel pathways in comparison with free space. Under VSC, reactions may be inhibited or catalyzed, or the product * Electronic address: felipe.herrera.u@usach.cl branching ratios tilted [7,16,22,23]. For instance, by strongly coupling the carbon-silyl (Si-C) bond stretching vibration of 1-phenyl-2-trimethylsilylacetylene to the electromagnetic vacuum of a resonant infrared microfluidic cavity, the rate of Si-C bond breakage has been shown to decrease by a moderate factor of order unity [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To describe chemical processes that are strongly correlated with quantum light [17][18][19] , requires an accurate and flexible, furthermore computationally efficient, treatment of the lightmatter interactions. Thus, in order to meet the demand of developing an ab initio theoretical description of cavity modified chemical systems, extensions to the traditional theoretical tool-kits for quantum optics and quantum chemistry are required.…”
Section: Introductionmentioning
confidence: 99%